If $x=a\sin 2t(1+\cos 2t)$ and $y=b\cos 2t(1-\cos 2t)$, show that at $t=\dfrac{\pi }{4}$,
$\dfrac{dy}{dx}=\dfrac{b}{a}$.
Answer
Verified
510.6k+ views
Hint: Take $x=a\sin 2t(1+\cos 2t)$ and $y=b\cos 2t(1-\cos 2t)$ and differentiate both of them w.r.t $t$ .After that, divide each other and substitute $t=\dfrac{\pi }{4}$. You will get the answer.
Complete step by step solution :
We are given $x=a\sin 2t(1+\cos 2t)$ and $y=b\cos 2t(1-\cos 2t)$.
So now differentiating $x$ w.r.t $t$ and differentiating $y$ w.r.t $t$ we get,
For $x$,
\[\begin{align}
& \dfrac{dx}{dt}=\dfrac{d}{dt}\left( a\sin 2t(1+\cos 2t) \right) \\
& \dfrac{dx}{dt}=a\sin 2t\dfrac{d}{dt}(1+\cos 2t)+a(1+\cos 2t)\dfrac{d}{dt}\sin 2t \\
& \dfrac{dx}{dt}=a\sin 2t(-2\sin 2t)+2a(1+\cos 2t)(\cos 2t) \\
& \dfrac{dx}{dt}=-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t) \\
\end{align}\]
\[\dfrac{dx}{dt}=-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t)\] …………… (1)
For $y$,
\[\begin{align}
& \dfrac{dy}{dt}=\dfrac{d}{dt}b\cos 2t(1-\cos 2t) \\
& \dfrac{dy}{dt}=b\cos 2t\dfrac{d}{dt}(1-\cos 2t)+b(1-\cos 2t)\dfrac{d}{dt}\cos 2t \\
& \dfrac{dy}{dt}=b\cos 2t(2\sin 2t)+b(1-\cos 2t)(-2\sin 2t) \\
& \dfrac{dy}{dt}=2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t) \\
\end{align}\]
\[\dfrac{dy}{dt}=2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)\]……………. (2)
Now dividing (2) by (1) we get,
\[\begin{align}
& \dfrac{\dfrac{dy}{dt}}{\dfrac{dx}{dt}}=\dfrac{2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)}{-2a{{\sin
}^{2}}2t+2a(1+\cos 2t)(\cos 2t)} \\
& \dfrac{dy}{dx}=\dfrac{2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)}{-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t)}
\\
\end{align}\]
Now substituting $t=\dfrac{\pi }{4}$in (1) and (2), we get,
\[\begin{align}
& \dfrac{dy}{dx}=\dfrac{2b\cos 2\left( \dfrac{\pi }{4} \right)\sin 2\left( \dfrac{\pi }{4} \right)-2b(1-\cos
2\left( \dfrac{\pi }{4} \right))(\sin 2\left( \dfrac{\pi }{4} \right))}{-2a{{\sin }^{2}}2\left( \dfrac{\pi }{4}
\right)+2a(1+\cos 2\left( \dfrac{\pi }{4} \right))(\cos 2\left( \dfrac{\pi }{4} \right))} \\
& \dfrac{dy}{dx}=\dfrac{2b\cos \left( \dfrac{\pi }{2} \right)\sin \left( \dfrac{\pi }{2} \right)-2b(1-\cos
\left( \dfrac{\pi }{2} \right))(\sin \left( \dfrac{\pi }{2} \right))}{-2a{{\sin }^{2}}\left( \dfrac{\pi }{2}
\right)+2a(1+\cos \left( \dfrac{\pi }{2} \right))(\cos \left( \dfrac{\pi }{2} \right))} \\
\end{align}\]………….
Now taking $2a$and $2b$ common we get,
\[\begin{align}
& \dfrac{dy}{dx}=\dfrac{2b}{2a}\left[ \dfrac{0-(1-0)(1)}{-1+0} \right] \\
& \dfrac{dy}{dx}=\dfrac{b}{a}\left[ \dfrac{-1}{-1} \right] \\
\end{align}\]
\[\dfrac{dy}{dx}=\dfrac{b}{a}\]
So we get, \[\dfrac{dy}{dx}=\dfrac{b}{a}\].
Hence proved.
Note: Read the question carefully. Don’t confuse yourself. Your concept regarding differentiation should be clear. Also, take care that while simplifying no terms are missed. Do not make any silly mistakes. While solving, take care that no signs are missed.
Complete step by step solution :
We are given $x=a\sin 2t(1+\cos 2t)$ and $y=b\cos 2t(1-\cos 2t)$.
So now differentiating $x$ w.r.t $t$ and differentiating $y$ w.r.t $t$ we get,
For $x$,
\[\begin{align}
& \dfrac{dx}{dt}=\dfrac{d}{dt}\left( a\sin 2t(1+\cos 2t) \right) \\
& \dfrac{dx}{dt}=a\sin 2t\dfrac{d}{dt}(1+\cos 2t)+a(1+\cos 2t)\dfrac{d}{dt}\sin 2t \\
& \dfrac{dx}{dt}=a\sin 2t(-2\sin 2t)+2a(1+\cos 2t)(\cos 2t) \\
& \dfrac{dx}{dt}=-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t) \\
\end{align}\]
\[\dfrac{dx}{dt}=-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t)\] …………… (1)
For $y$,
\[\begin{align}
& \dfrac{dy}{dt}=\dfrac{d}{dt}b\cos 2t(1-\cos 2t) \\
& \dfrac{dy}{dt}=b\cos 2t\dfrac{d}{dt}(1-\cos 2t)+b(1-\cos 2t)\dfrac{d}{dt}\cos 2t \\
& \dfrac{dy}{dt}=b\cos 2t(2\sin 2t)+b(1-\cos 2t)(-2\sin 2t) \\
& \dfrac{dy}{dt}=2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t) \\
\end{align}\]
\[\dfrac{dy}{dt}=2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)\]……………. (2)
Now dividing (2) by (1) we get,
\[\begin{align}
& \dfrac{\dfrac{dy}{dt}}{\dfrac{dx}{dt}}=\dfrac{2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)}{-2a{{\sin
}^{2}}2t+2a(1+\cos 2t)(\cos 2t)} \\
& \dfrac{dy}{dx}=\dfrac{2b\cos 2t\sin 2t-2b(1-\cos 2t)(\sin 2t)}{-2a{{\sin }^{2}}2t+2a(1+\cos 2t)(\cos 2t)}
\\
\end{align}\]
Now substituting $t=\dfrac{\pi }{4}$in (1) and (2), we get,
\[\begin{align}
& \dfrac{dy}{dx}=\dfrac{2b\cos 2\left( \dfrac{\pi }{4} \right)\sin 2\left( \dfrac{\pi }{4} \right)-2b(1-\cos
2\left( \dfrac{\pi }{4} \right))(\sin 2\left( \dfrac{\pi }{4} \right))}{-2a{{\sin }^{2}}2\left( \dfrac{\pi }{4}
\right)+2a(1+\cos 2\left( \dfrac{\pi }{4} \right))(\cos 2\left( \dfrac{\pi }{4} \right))} \\
& \dfrac{dy}{dx}=\dfrac{2b\cos \left( \dfrac{\pi }{2} \right)\sin \left( \dfrac{\pi }{2} \right)-2b(1-\cos
\left( \dfrac{\pi }{2} \right))(\sin \left( \dfrac{\pi }{2} \right))}{-2a{{\sin }^{2}}\left( \dfrac{\pi }{2}
\right)+2a(1+\cos \left( \dfrac{\pi }{2} \right))(\cos \left( \dfrac{\pi }{2} \right))} \\
\end{align}\]………….
Now taking $2a$and $2b$ common we get,
\[\begin{align}
& \dfrac{dy}{dx}=\dfrac{2b}{2a}\left[ \dfrac{0-(1-0)(1)}{-1+0} \right] \\
& \dfrac{dy}{dx}=\dfrac{b}{a}\left[ \dfrac{-1}{-1} \right] \\
\end{align}\]
\[\dfrac{dy}{dx}=\dfrac{b}{a}\]
So we get, \[\dfrac{dy}{dx}=\dfrac{b}{a}\].
Hence proved.
Note: Read the question carefully. Don’t confuse yourself. Your concept regarding differentiation should be clear. Also, take care that while simplifying no terms are missed. Do not make any silly mistakes. While solving, take care that no signs are missed.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Business Studies: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Trending doubts
Which are the Top 10 Largest Countries of the World?
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Draw a labelled sketch of the human eye class 12 physics CBSE
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
What is a transformer Explain the principle construction class 12 physics CBSE
What are the major means of transport Explain each class 12 social science CBSE